'n Godsleer van Openbaring soos vervat in die himnes - Meyer, E. (Verbum et ecclesia, 1997)
A Theology of Revelations as imbedded in the hymns. This anicle is based on a twofold hypothesis, namely that the author of Revelation not only wrote the hymns in this book,' he also used them specifically to express his theology. The narrator utilises the hymnes to lay words in the mouths of the characters in order to establish a complete theology as well as christology. These hymns can even be used today to offer mankind real hope by calling one and all to the centre and true reason for our existence: Worship God!